Evaluasi Program Belajar Dari Rumah (BDR) Pada Sekolah Dasar Dengan Menggunakan Model CIPP - Sahusilawane, Tiara Sulce; Ismanto, Bambang; Waruwu, Marinu (Kelola: Jurnal Manajemen Pendidikan, 2024)
This research aims to start a Home Learning (BDR) program at elementary schools in the city of Ambon including SDN Negeri Lama Ambon, SD Inpres 35 Passo and SD Inpres 53 Batugong. This research involved 39 informants. This type of research uses a qualitative descriptive approach with the CIPP (Context, Input, Process and Product) evaluation model. The subjects in this research were the principal, homeroom teacher for grades 1, 4 and 6. Students in grades 1, 4 and 6 and their parents from these three schools. Data collection techniques use interviews, observation and documentation studies. The data analysis techniques used include: Data collection, data reduction, data display and conclusions. The validation test in this research used source triangulation and technique triangulation. The results of the research show that in the context component the school has implemented it in accordance with the home learning program planning and technical guidelines from the government which have been adjusted to suit the needs of each school. The input component shows that there are fundamental differences between the three schools in terms of the availability of Human Resources, Facilities and Infrastructure and Financing. The process component shows that the implementation of BDR is carried out boldly and offline, where the implementation of online learning encounters a number of obstacles. The product component at the third school was considered less satisfactory than in previous years due to the limited input and learning processes found.